We need to solve the equation shown below for x:
[tex]\frac{1}{3}(2x-1)=z[/tex]Using distributive propery, a(b - c) = ab - ac , we can simplify the left hand side:
[tex]\begin{gathered} \frac{1}{3}(2x)-\frac{1}{3}(1)=z \\ \frac{2}{3}x-\frac{1}{3}=z \end{gathered}[/tex]We isolate the term with x and then divide the other side by 2/3 to get x = something...
[tex]\begin{gathered} \frac{2}{3}x-\frac{1}{3}=z \\ \frac{2}{3}x=z+\frac{1}{3} \\ x=\frac{z+\frac{1}{3}}{\frac{2}{3}} \end{gathered}[/tex]To simplify it (reduce), we can divide both terms by (2/3) and simplify. Shown below:
[tex]\begin{gathered} x=\frac{z}{\frac{2}{3}}+\frac{\frac{1}{3}}{\frac{2}{3}} \\ x=z\times\frac{3}{2}+\frac{1}{3}\times\frac{3}{2} \\ x=\frac{3z}{2}+\frac{1}{2} \\ x=\frac{3z+1}{2} \end{gathered}[/tex]The final answer:
[tex]x=\frac{3z+1}{2}[/tex]